KREATIVITAS GURU PAK MENGAJAK SISWA HIDUP DALAM KASIH MENURUT 1 KORINTUS 13:4-7 - Nainggolan, Denni Khas Juliana Br; Depari, Regita; Tambunan, Mida; Sembiring, Uli Anggraeni (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2022)
Students need to have love because they will be more readily accepted by the environment and pleasing to God. For students to have love, they need to be encouraged by CE teachers, and for that, CE teachers need to have creativity in encouraging students to have love, as stated in 1 Corinthians 4-7. This study aims to determine the effect of teacher creativity in inviting students to live in love according to 1 Corinthians 4-7 and its implications for changes in student behavior at school. The research subject is SMA Cerdas Bangsa, Medan, North Sumatra. The type of this research is quantitative. The sample involved was 30 students from different classes who were chosen randomly. The data was taken by distributing questionnaires to students. The study results stated a positive and significant correlation between the creativity of the CE teacher and the student's ability to live in love and changes in student behavior.